2007
DOI: 10.1562/0031-8655(2001)0740246pdspoh2.0.co2
|View full text |Cite
|
Sign up to set email alerts
|

pH-Dependent Spectral Properties of HpIX, TPPS2a, mTHPP and mTHPC¶

Abstract: Lower extracellular pH in tumors as compared to normal tissues has been proposed to be a factor contributing to the tumor selective uptake of several photosensitizers. Therefore, the pH dependence of absorption and fluorescence spectral properties of four different drugs relevant for photodynamic therapy (hematoporphyrin IX [HpIX], disulfonated meso‐tetraphenylporphine [TPPS2a], meso‐tetra(3‐hydroxyphenyl)porphine [mTHPP] and meso‐tetra(3‐hydroxyphenyl)chlorin [mTHPC]) has been examined. Spectral analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0
2

Year Published

2010
2010
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 18 publications
1
11
0
2
Order By: Relevance
“…The lower number of inflection points observed may be for the following reasons: (1) pK values may be separated by less than two pH, as suggested in other reports [7,16]; and (2) peripheral groups may slightly alter the absorption and fluorescence spectra [17].…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The lower number of inflection points observed may be for the following reasons: (1) pK values may be separated by less than two pH, as suggested in other reports [7,16]; and (2) peripheral groups may slightly alter the absorption and fluorescence spectra [17].…”
Section: Discussionmentioning
confidence: 67%
“…A number of studies on the acid-base properties of porphyrins and phthalocyanines have been reported [5][6][7][8], but no such study has been performed for Sn(IV) chlorin e6. The biochemical functions and activity of porphyrin-type molecules are governed by their physicochemical properties.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…O pH dos tecidos tumorais apresenta-se mais baixo do que o pH dos tecidos normais, este fato tem sido proposto como um fator que contribui para a captura seletiva pelo tumor dos diversos tipos de agentes fotossensíveis 48,92,93 . Na literatura a seletividade dos fotossensibilizadores por células tumorais é explicada pelo fato das células tumorais apresentarem grande número de receptores de lipoproteína que são os maiores transportadores de fotossensibilizadores.…”
Section: Espectroscopia De Absorção E De Fluorescênciaunclassified
“…Portanto, pequenas mudanças de pH do tecido podem levar ao deslocamento do equilíbrio entre as várias espécies iônicas do fotossensibilizador bem como sua protonação que pode estar relacionada com o aumento de sua lipofilicidade levando a uma maior captura do fotossensibilizador pelas células 48 . E sabendo que a maioria dos compostos utilizados em PDT são moléculas com estrutura semelhante a porfirina, que possuem sítios de protonação/desprotonação em sua estrutura molecular, é muito importante considerar o pH um dos fatores mais importantes para sua eficácia 48,92,93 . …”
Section: Espectroscopia De Absorção E De Fluorescênciaunclassified